Exploring Students’ Attribution: Why Did Students Fail in Their Online Basic Grammar Class? - - Lestari, Putri Indah (English Education Department, Universitas Islam Indonesia, 2023)
Grammar is one of the crucial components that must be mastered by English as a Foreign Language (EFL) students when they want to learn English. Undoubtedly, many students think grammar is quite challenging to understand and master. In an English Language Education Program at a private university in Central Java, Indonesia, many EFL students failed their Basic Grammar classes. Therefore, this study aims to explore the EFL students’ attributions or reasons for their failure in their Basic Grammar class. The data were gathered through a semi-structured interview with five EFL students who failed their Basic Grammar class. My preliminary results indicate some factors that cause them to fail in their Basic Grammar classes, such as the lack of knowledge, internet connection, and students’ factors. Recommendations for future research are discussed.